2018
DOI: 10.3233/jad-179926
|View full text |Cite
|
Sign up to set email alerts
|

From Cerebrospinal Fluid to Blood: The Third Wave of Fluid Biomarkers for Alzheimer’s Disease

Abstract: The past five years have seen an enormous development in the field of fluid biomarkers for Alzheimer's disease (AD) and related disorders. The proteins that constitute the foundation for the cerebrospinal fluid (CSF) tests for the classical AD pathologies are now being explored as potential blood-based biomarkers, thanks to the recent implementation of ultrasensitive measurement technologies in academic and clinical laboratories worldwide. The current blood-derived data are still less clear than those obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 89 publications
1
64
0
1
Order By: Relevance
“…30 15,25,27,32 In this study, we found a positive correlation at baseline between serum NFL and 25-hydroxyvitamin D. This was surprising as it contradicts a previously reported association between high serum 25hydroxyvitamin D and low CSF NFL. 16 There were also differences between the patient populations in the studies. 16 There were also differences between the patient populations in the studies.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…30 15,25,27,32 In this study, we found a positive correlation at baseline between serum NFL and 25-hydroxyvitamin D. This was surprising as it contradicts a previously reported association between high serum 25hydroxyvitamin D and low CSF NFL. 16 There were also differences between the patient populations in the studies. 16 There were also differences between the patient populations in the studies.…”
Section: Discussionmentioning
confidence: 97%
“…24 It is unlikely that differences between NFL measurements in serum and CSF have contributed to the discordant results, as the concentrations in serum and CSF have been shown to correlate strongly (correlation coefficients from 0.75 to 0.97) in patients with diseases of the central nervous system. 16 There were also differences between the patient populations in the studies. Sandberg et al included patients also with primary and secondary progressive MS, some of their patients used immunomodulatory drugs that were not used by the patients in our study, and the vitamin D status of their patients seemed to be lower and more variable (median 44, range 5-333 nmol/L).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in peripheral fluids, the concentration of metabolites associated with the physiopathology of neurodegenerative disorders is, in general, lower than in the CSF, and thus ultrasensitive platforms are required for their robust quantification . To date, most work has been conducted in the AD field, where biomarkers associated with tauopathy, amyloidosis or neuronal injury have been studied in plasma and serum . Yet, the diagnostic accuracy of blood‐based biomarkers of neurodegeneration and dementia so far does not significantly improve that of CSF‐based ones .…”
Section: Discussionmentioning
confidence: 99%